Система охоронної сигналізації на базі Wi-Fi сканера - Когогін, Я. М. (ХНУРЕ, 2025)
This work investigates the principle of operation of a Wi-Fi module in monitoring mode, the creation of a system that responds to malicious devices in the field of operation of such a sensor, and notifies about a threat. The result of the operation of system is the detection of devices, the comparison of their MAC address in the database and, in the absence of this device, the activation of the notification system
Keywords: охоронна сигналізація; Wi-Fi сканер